(untitled) - Richard J. Elzinga (Upper Saddle River, NJ, 2000)
The book provides a clear, accessible introduction to the world of insects. It addresses topics on an introductory level, condensing the diversity and complexity of insects and their influence upon the ecosystem into the useful framework.
Keywords: entomology